Oxidative stress and antioxidant status among neonates born to mothers with pre-eclampsia and their early outcome. (September 2014) - Namdev, Sunita; Bhat, Vishnu; Adhisivam, Bethou; Zachariah, Bobby
Abstract Objective: To study the oxidative stress and antioxidant status among neonates born to pre-eclamptic mothers and their role in the early outcome of these babies. Study design: This case control study was conducted at a tertiary care teaching hospital in South India. We included 75 neonates born to mothers with pre-eclampsia matched against 75 neonates born to mothers with normal blood pressure. Relevant antenatal and neonatal clinical data were collected for all babies. Levels of malondialdehyde (MDA) and total antioxidant status (TAS) were estimated in cord blood and oxidative stress was correlated with early neonatal outcome. Results: Oxidative stress was increased among cases compared to controls as evidenced by increased mean MDA levels (7.43 ± 1.21 versus 3.06 ± 0.69 µmol/L) and decreased mean TAS (742.15 ± 27.30 versus 829.26 ± 23.16 mmol/L). Level of oxidative stress correlated with poor neonatal outcome including sepsis, NEC and respiratory distress among cases. An MDA value of 8.68 µmol/L can be used as a cut-off, with sensitivity of 60% and specificity of 89.2%, to predict neonatal death among babies born to pre-eclamptic mothers. Conclusion: Oxidative stress is increased in neonates born to mothers with pre-eclampsia and useful in predicting outcome.